2017
DOI: 10.15282/jmes.11.2.2017.11.0245
|View full text |Cite
|
Sign up to set email alerts
|

Design optimization of a B-pillar for crashworthiness of vehicle side impact

Abstract: In this study, Hypermesh and Catia V5 software were adopted for finite element analysis (FEA) of a vehicle B-pillar. The design objectives were to optimise the B-Pillar such that the maximum displacement, weight, and maximum stress value of B-Pillar is minimised without compromising its yield strength and impact resistant properties. This is significant for the improvement of a vehicle's crashworthiness and ensuring the safety of passenger(s) during road accidents. This study initially analysed a given B-pilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…The results showed that the intrusion displacement and intrusion velocity of the optimized B-pillar were effectively reduced, thus improving the safety of passengers. Ikpe et al 8 proposed a reinforced B-pillar by adding extra steel plates to its inner surface and applying seam welding to ascertain their fusion. Compared with the original B-pillar, the maximum von Mises stress and instruction displacement of the reinforced B-pillar have been decreased; Krishna et al 9 used the advanced high-strength steel for B-pillar structure to enhance the energy absorption performance.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the intrusion displacement and intrusion velocity of the optimized B-pillar were effectively reduced, thus improving the safety of passengers. Ikpe et al 8 proposed a reinforced B-pillar by adding extra steel plates to its inner surface and applying seam welding to ascertain their fusion. Compared with the original B-pillar, the maximum von Mises stress and instruction displacement of the reinforced B-pillar have been decreased; Krishna et al 9 used the advanced high-strength steel for B-pillar structure to enhance the energy absorption performance.…”
Section: Introductionmentioning
confidence: 99%
“…However, assuming this approximation is valid, the angular acceleration of the piston will be zero. According to Ikpe et al [14], Von-mises stress criterion helps in predicting the yield point of a material when subjected to complex loading conditions. The Von-mises failure theory states that a given material under the influence of forces is prone to failure if the Von mises stress resulting from the reaction forces exceed the material yield strength, but if the Von-mises stress value is less than the material's yield strength, such material still has the capacity to accommodate additional forces [15].…”
Section: Resultsmentioning
confidence: 99%
“…For normal uniformly distributed wind loading on the blade, the maximum deflection was modelled using Equation (2). The equation is a typical deflection equation of an elastic cantilever system under uniformly distributed loads [10]. Where P = wL, w is uniformly distributed load along the blade cross section.…”
Section: Design and Development Of The Rotor Blade Modelsmentioning
confidence: 99%
“…where fe is the excitation frequency, fn is the natural frequency, is the damping ratio obtained from the logarithmic damping decrement given by Equation ( 9); = 2 (9) In conditions where the frequency of the excitation reduces significantly during operation, this can be expressed by the relation in Equation ( 10); = 2 (10) where designates circular frequency of the excitation, c is the local blade chord length and Urel is the local flow velocity relative to the blade section. Considering the time between amplitudes, the undamped ( ) and damped ( ) periods of vibration is given by Equations ( 11) and ( 12) respectively [14].…”
Section: Design and Development Of The Rotor Blade Modelsmentioning
confidence: 99%